In vitro Enzymatic Carbohydrate Digestion and Spectrophotometric Glycemic Indexes and Glycemic Loads Determination of Some Turkish Breads : in vitro Enzymatic Carbohydrate Digestion - Yusufoğlu, Büşra; Yaman, Mustafa; Karakuş, Emine (Progress in Nutrition, 2021)
Summary. Objective: Carbohydrates are the most abundant and common organic sources in nature. They are vital substances of whole living organisms. Bread is the main food source of people all over the world and very important issue in human diet as a source of carbohydrate. Bread is the principal food of Turkish People and daily average consumption is around 400 g per person. More than half of the caloric intake is supplied by bread. Besides protein and some vitamins, it’s a basic source of mineral supply in Turkish diet. Glycemic Index (GI) is glucose response of food as a percentage and it is generally made by in vivo methods and expressed as a value between 0 and 100. Foods with GI value more than 70 are (bad) carbonhydrates with high glycemic index. Glycemic load (GL), measures carbonhydrate amount in one portion of one food and gives truer results and is expressed this formula: GY=(GIxconsumed amount of carbonhydrates as gram)/100. Method: In this study, after digestion the variety of some breads commercially sold in our country in vitro conditions, the assays of GI and GL of these products were carried out with spectrophotometric based methods. Result: Whole wheat bread, wheat germ bread, hazelnut-grape bread, gluten-free bread and village bread were calculated using the values of GI and GY as reference carbohydrates using white bread. As a result, it was found that high wheat bread, wheat germ bread and hazelnut-grape bread have higher GI values than 70 (>70), gluten-free bread medium, and village bread was low glycemic index (<55). Conclusion: After that directly we determined glycemic load values of diffrent types of breads such as wheat bread, wheat germ bread and hazelnut-grape bread have higher GL values than (> 20).